Halal Industry in the Creative Economy: Opportunities in the Entertainment and Media Sectors - Mazaya Najmy Tsaqyfa; Nur Azzah Athirah Binti Sha’ari (ASEAN Journal of Halal Study, 2024)
The halal industry has grown significantly across various sectors, including food, cosmetics, and fashion. However, the halal entertainment and media sector remains underexplored, despite increasing demand from Muslim consumers for content aligned with Islamic values. This study aims to analyze the opportunities and challenges of developing the halal entertainment and media industry within the creative economy framework. The research employs a literature review method, examining secondary sources such as industry reports, academic articles, and relevant publications. The data were analyzed qualitatively to assess the growth of the halal entertainment industry, the impact of digital technology, and the regulatory challenges related to halal content certification. Findings indicate that digital technology, such as streaming platforms, plays a crucial role in expanding global access to halal content. Additionally, Muslim consumers increasingly prefer entertainment that aligns with Islamic values. However, major challenges include the lack of clear regulations and certification standards for halal entertainment, along with the creative limitations in producing content that is both appealing and compliant with Islamic principles. In conclusion, the halal entertainment and media industry holds significant potential, particularly in Muslim-majority countries like Indonesia. Clearer regulations and content innovation are key drivers for future growth.